2021
DOI: 10.1186/s12877-021-02426-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of frailty in older adult patients with chronic coronary syndrome: a cross-sectional study

Abstract: Background Frailty is an expression of vulnerability and decline of physical, mental, and social activities, more commonly found in older adults. It is also closely related to the occurrence and poor prognosis of coronary artery disease (CAD). Little investigation has been conducted on the prevalence and determinants of frailty in older adult patients with chronic coronary syndrome (CCS). Methods A cross-sectional study was conducted, simple random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 41 publications
2
14
0
3
Order By: Relevance
“…Our results showed that the prevalence of frailty among the studied elderly patients in China with CCS was 37.5%, thus suggesting that the prevalence of frailty was higher in elderly patients with CCS. Certain confirmation for our results comes from a cross‐sectional study in Eastern China 23 where the prevalence of frailty in 208 elderly patients (≥60 years old) with CCS was 30.3%. This estimation was slightly lower than our results; we consider that the difference in the frailty assessment tools and the regional differences between Eastern and Western China could be a possible explanation for this difference.…”
Section: Discussionsupporting
confidence: 77%
“…Our results showed that the prevalence of frailty among the studied elderly patients in China with CCS was 37.5%, thus suggesting that the prevalence of frailty was higher in elderly patients with CCS. Certain confirmation for our results comes from a cross‐sectional study in Eastern China 23 where the prevalence of frailty in 208 elderly patients (≥60 years old) with CCS was 30.3%. This estimation was slightly lower than our results; we consider that the difference in the frailty assessment tools and the regional differences between Eastern and Western China could be a possible explanation for this difference.…”
Section: Discussionsupporting
confidence: 77%
“…There is a strong intersection of FS and coronary artery disease (CAD) [ 20 , 21 , 57 ]. For example, the Women’s Health Initiative Study showed that women with CAD are more likely to develop de novo FS within six years than women without CAD [ 57 ].…”
Section: Fs and Coronary Artery Diseasementioning
confidence: 99%
“…For example, the Women’s Health Initiative Study showed that women with CAD are more likely to develop de novo FS within six years than women without CAD [ 57 ]. Lyu et al reported that the prevalence of FS in patients with chronic coronary syndrome was about 30%, and age, malnutrition, hearing dysfunction, depression, and venous thromboembolism risk were significantly associated with FS [ 20 ]. Moreover, about half of patients with non-ST-elevation myocardial infarction have FS, which is associated with an increased risk of recurrent myocardial infarction, revascularization, hospitalization, bleeding, stroke, dialysis, and mortality, compared to patients without FS [ 22 ].…”
Section: Fs and Coronary Artery Diseasementioning
confidence: 99%
See 2 more Smart Citations